Revitalisation of the Performing Arts in the Ancestral Homeland of Lampung People, Sumatra - Karen Kartomi Thomas, (Wacana Seni Journal of Arts Discourse, 2014)
Lampung's ethno-lingual groups turned their attentions to reviving their performing arts more than two decades ago, activities which gained momentum after 2004 when the newly elected governor of the province Sjachroedin ZP instigated a revitalisation (revitalisasi) cultural program. Lampung's minority indigenous population resulted from large-scale transmigrations especially from Java that began under Dutch rule from 1908 and continued well after independence and into the present. With encouragement from the government regents (bupati) in the province's regions sought concrete ways to revive and promote the local arts. In West Lampung they arranged the staging of both traditional and modern contemporary forms in ceremonial processions and festivals that take place on significant holidays such as Independence Day celebrations, regional government official welcoming ceremonies, and other large-scale local festivities including the week leading up to the end of the Muslim Fasting month (Idul Fitri or Lebaran).The indigenous people of Lampung (ulun Lampung) divide into Saibatin and Pepadun categories. The Saibatin group consists of the Peminggir (coastal) people, as they have been known since the Dutch colonial period (Funke 1961). Groups living inland and in the mountainous areas known as Abung and Pubian, when grouped together, are also referred to as Pepadun (other spellings include Papadun and Papadon). The effects on the performing arts of the directive from Lampung's governor through to the regents of Saibatin ethnic groups in the Skala Brak area in the province's mountainous northwest are examined. All of Lampung's ethno-lingual groups recognise Skala Brak—located around the province's highest Mount Pesagi—as their ancestral homeland. It is Skala Brak's distinctive performing arts—including the sakura masked theatre and its variations, and two well-known local female dances, muli sembah (welcoming dance) and sigeh pengutin (long fingernail dance) that have been revitalised and refashioned as new Saibatin creations (I., kreasi baru).